1997
DOI: 10.1055/s-0038-1656003
|View full text |Cite
|
Sign up to set email alerts
|

The Urokinase-receptor (CD87) Is Expressed in Cells of the Megakaryoblastic Lineage

Abstract: SummaryMegakaryocytopoiesis is governed in the bone marrow microenvironment by cellular interactions that include various adhesion receptor systems and pericellular proteolysis for proper regulation of cell motility and differentiation. In order to define the role of cell surface molecules required for these processes, we searched for protease receptors on these cells. In an in vitro system utilizing different cell lines of the megakaryoblastic lineage (MEG-01, Dami), low level surface expression of the urokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 60 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…To date, it is unclear how suPAR is formed. As mononuclear cells and neutrophils exhibit uPAR expression, it was proposed that suPAR in healthy individuals may be derived from cell ageing, cell death, differentiation of the bone marrow, and the formation of megakaryocytes and platelets (23,24). Previous studies have also demonstrated that the elevated suPAR levels, observed in patients with cancer, are associated with a poor outcome (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is unclear how suPAR is formed. As mononuclear cells and neutrophils exhibit uPAR expression, it was proposed that suPAR in healthy individuals may be derived from cell ageing, cell death, differentiation of the bone marrow, and the formation of megakaryocytes and platelets (23,24). Previous studies have also demonstrated that the elevated suPAR levels, observed in patients with cancer, are associated with a poor outcome (25).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 uPAR is expressed by a wide range of immune cells whereas suPAR can be detected in different body fluids, including serum and plasma. [11][12][13][14][15][16][17] Cell-surface uPAR expression is up-regulated upon stimulation with growth factors and cytokines such as interleukin-1β and tumor necrosis factor. 18,19 The full length suPAR shed from the cell surface contains three domains (DI-III), and suPAR can occur in different cleaved forms consisting of only DI or DII-III, with partly divergent biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…uPAR is known to be displayed on the surface of human blood monocytes and neutrophils (Plesner et al, 1997), so that senescence of these cells could be one source of suPAR in blood. The differentiation of megakaryocytes and formation of platelets in bone marrow may also contribute significant levels of suPAR to the blood compartment (Wohn et al, 1997).…”
mentioning
confidence: 99%